Prevalence of cognitive impairment among Hungarian patients with relapsing-remitting multiple sclerosis and clinically isolated syndrome - Sandi Dániel; Biernacki Tamás; Szekeres Dóra; Füvesi Judit; Kincses Zsigmond Tamás; Rózsa Csilla; Mátyás Klotild; Kása Krisztián; Matolcsi Judit; Zboznovits Dóra; Burány Zita; Langane Éva; et al. (Springer-Verlag London Ltd, 2017)
Background Cognitive impairment (CI) is a frequent symptom of multiple sclerosis (MS); its prevalence is reported to be 43–70%. It is one of the most important determinants of MS patients’ quality of life, as it is one of the main factors for MS patients becoming unemployed. Aim We aimed to determine the prevalence of CI among the relapsing-remitting MS (RRMS) and clinically isolated syndrome (CIS) patients in Hungary, to evaluate the predicting factors of CI and to assess the differences between sexes and patients with different educational levels. Patients and methods Five-hundred and fifty-three CIS and RRMS patients were enrolled to our study from three Hungarian MS centers. Age at screening, age at disease onset, disease duration, EDSS score, sex and educational levels were analyzed as socio-demographic factors. The BICAMS battery was used to assess their cognitive state, the BDI-II battery to assess depression. For statistical analysis, we utilized logistical regression, and used Fisher exact tests, chi-square tests and one-way ANOVA. Results The mean age of our patients was 44.93 ± 11.69 years, mean age at disease onset was 31.95 ± 10.01 years, the mean disease duration was 13.05 ± 8.05 years and the median EDSS score 2.0 (Range: 6.5, IQR:2.0) points. Three-hundred and sixteen (57.1%) patients had CI. Sex, educational level and EDSS score proved to be significant predictors of CI (OR: 2.71, p < 0.001; OR: 1.94, p = 0.023; OR: 0.47, p = 0.003 respectively). CI was significantly (p < 0.001) more frequent among men (70.1%) than women (52.0%). We found, that educational level and EDSS score were only a significant predicting factor among women. Thus, the prevalence of CI among women with college or university degree was significantly (p < 0.001) less common (39.4%) than women with 12–15 years of education (57.4%) and women without a high school degree (66.7%). Also, we found that among women with higher EDSS score than 2 points, the prevalence of CI is 69.9% as compared to women with EDSS score between 0 and 2 points, where the prevalence is 42.8% (p < 0.001). No such differences were observed among man. Discussion Our prevalence data is similar to those reported in the literature (43–70%), and almost identical to the one assessment using the BICAMS battery. We found that men are more vulnerable to CI than women in MS, as was reported recently. We are the first to report however, that higher educational level and lower EDSS scores are only associated with better cognitive performance in women. © 2017